Comparative study of Riau Pos and the Star Media implementation in convergence continuum - Yazid, Tantri; Salsabila, Salsabila (Faculty of Communications Science, Dr. Soetomo University, 2023)
In this day, media competition using technologies is competing to provide and reach the reader. Technologies are developing, and every medium has its own way of growing its activities. This study uses a qualitative method with the Continuum Convergence theory belonging to Daily, Demo, Spillman, and the management concept. The subjects in this study are two media companies named Riau Pos and The Star that compared to understand how media has been carrying out the implementation of Continuum Convergence to maintain its existence in the phenomena that occur, as well as see how the management side and compare it with other media implementation. This research found that Riau Pos and The Star have some differences and similarities in their implementation of continuum convergence. Point out how Riau Pos and The Star differ in managing social media and integrating the technologies.